Structure Differentiation of Hydrophilic Brass Nanoparticles Using a Polyol Toolbox - Antonoglou, Orestis; Founta, Evangelia; Karagkounis, Vasilis; Pavlidou, Eleni; Litsardakis, George; Mourdikoudis, Stefanos; Thanh, Nguyen Thi Kim; Dendrinou-Samara, Catherine (Frontiers in Chemistry, 2019)
Nano-brasses are emerging as a new class of composition-dependent applicable materials. It remains a challenge to synthesize hydrophilic brass nanoparticles (NPs) and further exploit them for promising bio-applications. Based on red/ox potential of polyol and nitrate salts precursors, a series of hydrophilic brass formulations of different nanoarchitectures was prepared and characterized. Self-assembly synthesis was performed in the presence of triethylene glycol (TrEG) and nitrate precursors Cu(NO3)2·3H2O and Zn(NO3)2·6H2O in an autoclave system, at different temperatures, conventional or microwave-assisted heating, while a range of precursor ratios was investigated. NPs were thoroughly characterized via X-ray diffraction (XRD), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), transmition electron microscopy (TEM), Fourier-transform infrared (FTIR) spectroscopy, dynamic light scattering (DLS), and ζ-potential to determine the crystal structure, composition, morphology, size, state of polyol coating, and aqueous colloidal stability. Distinct bimetallic α-brasses and γ-brasses, α-Cu40Zn25/γ-Cu11Zn24, α-Cu63Zn37, α-Cu47Zn10/γ-Cu19Zn24, and hierarchical core/shell structures, α-Cu59Zn30@(ZnO)11, Cu35Zn16@(ZnO)49, α-Cu37Zn18@(ZnO)45, Cu@Zinc oxalate, were produced by each synthetic protocol as stoichiometric, copper-rich, and/or zinc-rich nanomaterials. TEM sizes were estimated at 20–40 nm for pure bimetallic particles and at 45–70 nm for hierarchical core/shell structures. Crystallite sizes for the bimetallic nanocrystals were found ca. 30–45 nm, while in the case of the core-shell structures, smaller values around 15–20 nm were calculated for the ZnO shells. Oxidation and/or fragmentation of TrEG was unveiled and attributed to the different fabrication routes and formation mechanisms. All NPs were hydrophilic with 20–30% w/w of polyol coating, non-ionic colloidal stabilization (−5 mV < ζ-potential < −13 mV) and relatively small hydrodynamic sizes (<250 nm). The polyol toolbox proved effective in tailoring the structure and composition of hydrophilic brass NPs while keeping the crystallite and hydrodynamic sizes fixed.